Auditoria de gestión al proceso de recaudación y cancelación de las pensiones alimenticias en la pagaduría de los juzgados segundo, segundo adjunto y tercero de la familia mujer niñez y adolescencia de Quevedo, periodo 2012 - Cedeño Barros, Verónica Roxana (2013)
The correct analysis of maintenance payments in different courts for children and family, since its inception has been an ideal method to solve problems between people, in a more informal common ordinary proceedings, as well as grants the parties involved one protagonist intervention in resolving their conflicts. This document has structured in 7 chapters, starting with the same introductory aspects, then develops the theme to develop the conclusions and final recommendations. In the first chapter of this paper explores the conflict, the objectives for which they must lead this study and formulate a hypothesis, to further deepen the solution of the research problem. In order to analyze the situation and problems of management system of child support payments in the juvenile courts and the Ecuadorian family, specifically in the city of Quevedo, in the second chapter, where a literary analysis was compiled the necessary information from the courts under study, and their bodies and auxiliary. For further analysis of the study population and sample together with experimental research design was used to determine this research work, this was developed in chapter three of this thesis. In order to quantify the existing processes and how they take to resolve them, in chapter four we find the results and discussions and this is where you have the greatest weaknesses of the pension payment system in the courts for children and adolescents Ecuadorian to establish the results so far have been obtained and determine if known possibilities will be a larger number of cases from the procedural shunt study. In the final chapter of this study indicated the different references used in the theoretical framework of this research.